PENERAPAN MEDIA FLASHCARD UNTUK MENINGKATKAN PEMAHAMAN TERHADAP KALIMAT “I LIKE” DAN “I DON’T LIKE” PADA PELAJARAN BAHASA INGGRIS SISWA KELAS III SDN KARANGTUMARITIS 1 - Ade Dina Nurkhakiki; Putri Intan Syamsudin; Fadhil Abu Jihad; Juhdan Abdullah Mu’arif; Dewi Nopasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
English, as an international language, plays a crucial role in learning from elementary school. However, limited resources and limited exposure to foreign languages ​​often hinder learning. One approach teacher can take is to utilize visual media such as flashcards, which can help students understand vocabulary through concrete representations. This study aims to analyze the effectiveness of using flashcards in improving third-grade students' understanding of simple vocabulary and the sentence patterns